Differentiation: the case of industrial enterprises - Chirinos-Cuadros, Carlos Ricardo (2016)
In a global market with high demands to satisfy the consumer, industrial companies have chosen differentiation as a generic strategy. The success of a differentiated company lies in the development of exceptional attributes of the product and the performance of processes with a clear focus on service. This article seeks to deploy the differentiation strategy along four activities of the value chain: product design, procurement, processing and transportation.